2022
DOI: 10.1002/pon.5881
|View full text |Cite
|
Sign up to set email alerts
|

Risk of major depressive disorder in adolescent and young adult cancer patients in Japan

Abstract: Objective To estimate the risk of major depressive disorder (MDD) in adolescent and young adult (AYA) patients with cancer in Japan and identify risk factors for MDD among these patients. Methods This was a matched cohort study using a large claims database in Japan. Included patients were aged 15–39 years, newly diagnosed with cancer during 2012–2017 and assessable for a follow‐up period of 12 months. Kaplan–Meier estimates and Cox proportional hazards models were used to calculate hazard ratios (HR) and 95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Meta-analyses were performed to evaluate the risk of developing severe depression or a depressive disorder and the mean severity of depressive symptoms in CYACs . The specific scales used to measure depressive symptomatology are presented in eTable 3 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meta-analyses were performed to evaluate the risk of developing severe depression or a depressive disorder and the mean severity of depressive symptoms in CYACs . The specific scales used to measure depressive symptomatology are presented in eTable 3 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
“…Incidence and RRs in CYACs and controls without cancer for severe depression or depressive disorder (A), severe anxiety or anxiety disorder (B), and psychotic disorders (C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for treatment status, 38.2% of the studies recruited participants who were off treatment at the assessment time. 24,25,27,30,[32][33][34][35][36]39,[42][43][44]46,47,50,53,57,60,61,65,67,68,70,79,85 Regarding study quality, only four (5.9%) 53,59,64,88 were considered of very good and 17 (25.9%) 22,25,33,38,[42][43][44]50,52,57,62,66,68,71,72,81,90 of good quality. The rest of the studies were rated as satisfactory (47%) or unsatisfactory (22.1%) (Table 1 and eTable 4).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In a questionnaire survey in Japan, pain, decrease in income after a cancer diagnosis, experience of negative changes at work or school after a cancer diagnosis, and poor social support were reported to be significantly associated with psychological distress [ 14 ]. Furthermore, AYA patients with cancer in Japan have a three-fold higher risk of major depressive disorder within 6 months before and 12 months after cancer diagnosis compared with cancer-free controls [ 15 ]. A previous study found that AYA patients with cancer aged 15–24 years have a higher risk of suicide than cancer-free controls [ 16 ].…”
Section: Introductionmentioning
confidence: 99%